Opportunities to Target the Life Cycle of Epstein-Barr Virus (EBV) in EBV-Associated Lymphoproliferative Disorders - Dugan, James P.; Coleman, Carrie B.; Haverkos, Bradley (Frontiers in Oncology, 2019)
Many lymphoproliferative disorders (LPDs) are considered “EBV associated” based on detection of the virus in tumor tissue. EBV drives proliferation of LPDs via expression of the viral latent genes and many pre-clinical and clinical studies have shown EBV-associated LPDs can be treated by exploiting the viral life cycle. After a brief review of EBV virology and the natural life cycle within a host we will discuss the importance of the viral gene programs expressed during specific viral phases, as well as within immunocompetent versus immunocompromised hosts and corresponding EBV-associated LPDs. We will then review established and emerging treatment approaches for EBV-associated LPDs based on EBV gene expression programs. Patients with EBV-associated LPDs can have a poor performance status, multiple comorbidities, and/or are immunocompromised from organ transplantation, autoimmune disease, or other congenital or acquired immunodeficiency making them poor candidates to receive intensive cytotoxic chemotherapy. With the emergence of EBV-directed therapy there is hope that we can devise more effective therapies that confer milder toxicity.